2022
DOI: 10.1155/2022/4277254
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Topoisomerase II-α Regulated by miR-22-5p Promotes Hepatocellular Carcinoma Invasion and Migration through the Hippo Pathway

Abstract: DNA topoisomerases (TOPs) are dysregulated in various types of cancer. However, how TOP II-alpha (TOP2A) contributes to hepatocellular carcinoma (HCC) progression remains elusive. Cohort analysis revealed that the increased expression of TOP2A was associated with poor clinical outcomes and TOP2A was significantly upregulated in HCC tissues and cell lines. In vitro, TOP2A expression level is related to cell invasion and migration, which may be due to the alteration of epithelial-mesenchymal transition by the TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…TOP IIα is related to cancer cell growth, invasion, and metastasis. 28 TOP IIα is revealed to correlate with higher Gleason scores, higher levels of preoperative PSA and shorter biochemical recurrence-free survival in prostate cancer patients. 29 In contrast, TOP IIβ is also expressed in nondividing F I G U R E 7 Effect of WC-A derivatives on DNA repair-related proteins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TOP IIα is related to cancer cell growth, invasion, and metastasis. 28 TOP IIα is revealed to correlate with higher Gleason scores, higher levels of preoperative PSA and shorter biochemical recurrence-free survival in prostate cancer patients. 29 In contrast, TOP IIβ is also expressed in nondividing F I G U R E 7 Effect of WC-A derivatives on DNA repair-related proteins.…”
Section: Discussionmentioning
confidence: 97%
“…TOP IIα and TOP IIβ are two subclasses of TOP II. TOP IIα is related to cancer cell growth, invasion, and metastasis 28 . TOP IIα is revealed to correlate with higher Gleason scores, higher levels of preoperative PSA and shorter biochemical recurrence‐free survival in prostate cancer patients 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that miR-22-5p downregulation contributed to the malignant progression of non-small-cell lung cancer by targeting transcription factor TWIST2 [53]. miR-22-5p may also inhibit tumor progression by sponging DNA topoisomerase II-alpha [54].…”
Section: Microrna 22-5pmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%